ABRAHAM DI TENGAH PLURALITAS - Tundu, Surianti (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2024)
This study focuses on how Abraham's attitude in the narrative of Genesis 14:17-24 can serve as a theological example in addressing cultural and religious plurality, particularly in Indonesia's diverse context. The object of the research is the text of Genesis 14:17-24, analyzed to uncover its relevance to efforts in maintaining plurality in Indonesia. The research aims to highlight sympathetic narratives toward plurality in the Old Testament and how they can be applied in societal life. This study employs a qualitative method with narrative criticism and historical criticism approaches. Narrative criticism analyzes the structure and dynamics of the narrative, such as characters, symbols, and conflicts within the text. Meanwhile, historical criticism is used to understand the socio-historical context of the Israelites, including their interactions with the cultures and religions in Canaan. Data were collected from textual analysis of the Bible and literature on plurality in Indonesia, which were then analyzed interpretatively. The findings reveal that Abraham demonstrated a sympathetic and accommodative attitude toward plurality, such as receiving blessings from Melchizedek, using the name El Elyon, and refraining from confrontational behaviour toward Canaanite local culture. These attitudes reflect values of tolerance and moderation in diversity. In conclusion, this narrative is relevant to addressing the challenges of intolerance in Indonesia and inspires churches and society to promote harmony amidst plurality.